Inovasi Pelayanan Akta Kematian Online melalui Aplikasi Adminduk Online Makin Oke (AKOne MAK’e) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukoharjo - Desi Tri Wulandari; Herwan Parwiyanto (Jurnal Mahasiswa Wacana Publik, 2021)
Death certificate is a population administration document that must be owned by the community. The management of death certificates is generally carried out at the Population and Civil Registration Service. Sukoharjo Regency is classified as low in the management of Death Certificates, this is because public awareness is not high yet. The Department of Population and Civil Registration of Sukoharjo Regency launched an Android-based innovation, namely the AKOne MAK'e Application (Adminduk Online Makin Oke) in order to improve the quality of service to the community. This study aims to analyze innovation, factors supporting innovation and inhibiting factors for innovation in Death Certificate services through the AKOne MAK'e Application at the Population and Civil Registration Office of Sukoharjo Regency. This research is a descriptive qualitative research. The data from this study were obtained from interviews, observations and documentation at the Department of Population and Civil Registration of Sukoharjo Regency. The analysis of this study uses the five indicators of public service innovation proposed by Rogers, the supporting factors for innovation proposed by Everet M. Rogers and the inhibiting factors for innovation proposed by Borins and Drucker and refers to the data analysis model proposed by Miles and Huberman. The results of the study indicate that the innovation of online Death Certificate services through the AKOne MAK'e Application has relative advantages, compability, complexity, triability and observability. The supporting factors of service innovation are the desire to change themselves and the availability of adequate facilities and infrastructure. The service innovation has an inhibiting factor, namely public understanding of the procedures or mechanisms that are still low.